Fabrication of proton exchange membranes and effect of sulfonated SiO2 (S-SiO2) in sulfonated polyether ether ketone (SPEEK) for fuel cells applications. (November 2019) - Ali, Mawlood Maajal; Rizvi, S. J. A.; Azam, Ameer
Abstract: The fabrication of composite proton exchange membrane from the sulfonated polyether ether ketone (SPEEK) and sulfonated SiO2 (S-SiO2 ) have been investigated for energy production. In this work, inorganic fillers have been incorporated successfully in the organic polymer matrix. The degree of sulfonation (DS) and ion exchange capacity (IEC) were measured by back titration method and observed around 46.4 % and 1.43 mmol/gm, respectively. DS and IEC were found is increase with the increase of the amount of S-SiO2 which reached to 56.5 % and 1.69 mmol/gm, respectively. Water uptake in percent was increased in the SPEEK/S-SiO2 membrane due to increasing the sulfuric acid groups (-SO3 H), that lead to increasing the hydrophilic channels, the swelling ratio in percent was slightly increased. The proton conductivity of the SPEEK membrane was around 17.4 mS/cm and increased with increasing the amount of S-SiO2 . The highest proton conductivity observed at SPEEK/0.3 S-SiO2 was around 53.7 mS/cm. suggesting its use in fuel cell for energy production.